If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6a-5+3a=4a-3
We simplify the equation to the form, which is simple to understand
6a-5+3a=4a-3
We move all terms containing a to the left and all other terms to the right.
+6a+3a-4a=-3+5
We simplify left and right side of the equation.
+5a=+2
We divide both sides of the equation by 5 to get a.
a=0.4
| -4v/7=-24 | | 1/3x-1/4(x-2)=4x | | -9/5=3y | | .36X+.035Y=.10 | | 2(Z-38)=5(Z-59) | | 11/15-(-3/5) | | 3/4n=-24 | | -5/8v=10 | | x^2+9t+4=0 | | 36X/16+3.5Y/16=10 | | .6(15c+10)=12c-9 | | 25.6=y/8 | | 6/5x-1/11=-6 | | 1/7x+1/3y | | -3(x-8)-5=9*(x+2)+1 | | 7a-4+29=3a-2 | | 36X+3.5Y=10 | | -6(6-x)+6=12-8(x+2) | | 6/5x-1/11=6 | | 2/3/4/5 | | 7u=14/3 | | (6x+2)+2(3x-5)+(x+10)= | | 4/7x=56 | | 3x+3=7x-23 | | x+4/5=-1/6 | | 160-36X=3.5Y | | 1/z-1/5z-1/4z=20/z+1 | | 4=-3/8+x | | 2-4(x+3)=7x-10 | | 4x/3-1=0 | | 5-(2x+7)= | | w-1/4=-5/8 |